AgetEm - Prototyping of a new spirit vinegar - Laranjeira, Cristina (2021)
Agrio line of the AgetEm project (POCI-01-0145-FEDER-023583) aimed to develop new vinegar products, benefiting from the location of ESAS in Ribatejo, close to the main Portuguese vinegar industries. An innovative spirit vinegar prototype was developed (2017- 2019), by acetification of a monovarietal white wine distillate, produced from Talia grapes of the National Ampelographic Collection (Portugal). In the EU, “vinegar” is obtained exclusively by double alcoholic and acetic fermentation of substances of agricultural origin (EN 13188: 2000); however, it may include a distillation operation, as in alcohol vinegar or in distilled malt vinegar. Vinegar industry is a classic example of sustainability in the use of raw materials, positioning itself at the end of the agri-food transformation line.